Twenty years of research on cerato-platanin family proteins: clues, conclusions, and unsolved issues. Issue 1 (March 2020) - Luti, Simone; Sella, Luca; Quarantin, Alessandra; Pazzagli, Luigia; Baccelli, Ivan
Abstract: Twenty years of research on cerato-platanin family proteins (CPPs) have led to some clear conclusions: CPPs are exclusively present in the fungal kingdom and possess an outstanding capacity to stimulate the immune system of plants. Recent discoveries have highlighted remarkable structural and functional similarities between CPPs and expansins, a class of non-enzymatic proteins found in both plants and microbes possessing loosening ability on the cell wall structure. Nevertheless, the determination of a biological role for CPPs in fungi is becoming a complicated puzzle to solve, since experimental data are often divergent and point to functional diversification. A general consensus appears however possible: CPPs from pathogenic and beneficial fungi may be considered as microbe-associated molecular patterns (MAMPs) and likely play a dual role, exerting functions in the fungal cell wall and/or in plant colonization. In this review, which celebrates 20 y of research on CPPs, we trace the history of these proteins and highlight experimental evidence and still unsolved issues.